Propagation of a gravity current in an aquatic canopy: Insights from Large Eddy Simulations - Ozan, A. Yuksel; Constantinescu, G.; Tokyay, T. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2012)
Gravity currents forming on the bottom of rivers can encounter porous-like regions in which their propagation is slowed down due to the presence of natural or man-made obstacles. A classical example is the case of a vegetated canopy. Large Eddy Simulation (LES) is used to investigate the evolution of lock-exchange gravity currents with a high and a small volume of release propagating through a porous channel. The porous medium consists of an array of staggered cylinders of same diameter that are uniformly distributed over the whole depth and length of the channel. For the case of currents with a high volume of release, LES shows that low Reynolds number currents transition to a drag-dominated regime in which the front velocity, U-f, is proportional with t(-1/2), where t is the time measured starting at the release time. This power law exponential decay and its coefficient are in agreement with experiment and shallow water theory. By contrast, high Reynolds number currents with a high volume of release, for which the cylinder Reynolds number (Red) is high enough such that the drag coefficient on the cylinders can be considered constant, transition first to a drag dominated regime in which U-f similar to t(-0.25). The paper provides an explanation why the exponential decay parameter beta = -0.25 predicted for high Reynolds number currents is slightly different from the value predicted by shallow water theory (beta = -0.33). For the case of high Reynolds number gravity currents with a low volume of release and a sufficiently small ratio between the initial height of the lock fluid and the channel depth, H/H-c, LES predicts U-f similar to t(-1/2) during the drag dominated regime, which is in agreement with shallow water theory for H/H-c << 1. For the full depth of release case, LES predicts U-f similar to t(-3/5).
Keywords: LOCK-EXCHANGE; Engineering; Water Resources